Analysis of College Students' Critical Thinking Skills in Learning Physics Case Method Assisted by Lumio by SMART - Anggraeni, Firdha Kusuma Ayu; Prihandono, Trapsilo (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2025)
The critical thinking skills of education students need further enhancement. Critical thinking can be fostered through physics instruction using the case method, which links physics concepts to real-life situations. This approach is expected to improve students' critical thinking skills. Furthermore, in line with the needs of today's learners, integrating technology is essential. Lumio by SMART offers a dynamic platform to engage students, making learning more interactive and participatory. This descriptive study aimed to analyze students' critical thinking skills and their responses to the use of Lumio by SMART. The analysis was based on critical thinking skills scores and student feedback. The results demonstrated a significant improvement in students' critical thinking skills, as evidenced by the increase in post-test scores compared to pretest scores. Additionally, student responses were overwhelmingly positive. These findings suggest that the use of the case method, enhanced by Lumio by SMART, is effective in improving critical thinking skills. Thus, educators should incorporate the case method in their teaching to develop critical thinking and other cognitive skills, while leveraging technology to boost student engagement.